Ascending aorta over-angulation is a risk factor for acute type A aortic dissection: evidence from advanced finite element simulations - Ianniruberto, Ione; Lo Presti, Federica; Bifulco, Olimpia; Tondi, Davide; Saitta, Simone; Astori, Davide; Galgano, Viviana L; De Feo, Marisa; Redaelli, Alberto; Di Eusanio, Marco; Votta, Emiliano; Della Corte, Alessandro (European journal of cardio-thoracic surgery, 2025)
To assess whether ascending aorta over-angulation, a morphological feature recently found to be associated with acute type A aortic dissection, precedes dissection and how it affects wall stress distribution. A baseline finite element model, previously created by a neural network tool from end-diastolic computed tomography angiography measurements in 124 healthy subjects, was modified to simulate the over-angulation accompanying aortic elongation, obtaining paradigmatic models with different ascending angulations (ascending-arch angle 145°-110°). The models were discretized and embedded in a deformable continuum representing surrounding tissues, aortic wall anisotropy and nonlinearity were accounted for, pre-tensioning at diastolic pressures was applied and peak systolic stresses were computed. Then, from 15 patients' pre-dissection geometries, patient-specific finite element models of pre-dissection aorta were created through the same framework. The sites of maximum longitudinal stress were compared with the respective sites of dissection entry tear in post-dissection imaging. Paradigmatic models showed that progressive narrowing of the ascending-arch angle was associated with increasing longitudinal stress (becoming significant for angles <130°), whereas the impact on circumferential stress was less consistent. In pre-dissection patient-specific models, the ascending-arch angle was narrowed (113°±11°), and the region of peak longitudinal stresses corresponded to the entry tear location in the respective post-dissection computed tomography angiography. This study strongly supports the hypothesis that the ascending-arch angle, as quantifier of aorta over-angulation, can be a good predictor of aortic dissection, since its narrowing below 130° increases longitudinal wall stress, and the dissection entry tears develop in the aortic wall in areas of highest longitudinal stress.